THE ISSUE OF TRUCK BRAKING, THEIR ACCIDENT RATE AND ECONOMIC LOSSES INCURRED IN TRAFFIC ACCIDENTS IN THE CZECH REPUBLIC - Jiri Prnka; Lukas Zemanek; Michal Novotny (European Scientific Journal, ESJ, 2014)
The article's theme is the issue of truck braking, their accident rate and economic losses that incur in relation to traffic accidents in the Czech Republic. First, the issue of the accident rate of trucks is outlined here, as well as the consequences of traffic accidents relating to them, development of accident rate of truck drivers between 2006 and 2012, and then the economic losses incurred in traffic accidents are outlined here depending on the type of injury or damage. Then this article introduces the issue of legislation requirements for truck brakes and the results of the performed measurement of braking of trucks and truck trains going in a straight direction depending on the load, as well as braking of trucks with/without ABS and last but not least, truck braking when driving in a curve.